2008
DOI: 10.1080/10402000802011760
|View full text |Cite
|
Sign up to set email alerts
|

Role of Al2O3 in Semi-Metallic Friction Materials and its Effects on Friction and Wear Performance

Abstract: In this work the semi-metallic friction composites with moderately increased content of Al 2 O 3 (0, 3.4, 5.6, 9.0, and 14.6 vol%) were successfully fabricated by casting technology and their tribological properties were evaluated. The character of friction surfaces was confirmed by SEM. The sample with 5.6 vol% of Al 2 O 3 offers the best tribological property among the prepared formulations, and is characterized by high and steady friction coefficient (about 0.45) and low wear. With the temperature increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…There are two basic categories of friction materials for an automotive brake lining application, semi-metallic and non-asbestos organic (NAO). 1,2 Asbestos has been used for a long time in brake linings, but strictly prohibited due to its carcinogenicity in recent years. 3 Semi-metallic friction composites, as the most common brake lining materials, usually consist of a high amount of metallic components (typically >50%), covering iron powders, copper fibers, brass chips, molybdenite, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…There are two basic categories of friction materials for an automotive brake lining application, semi-metallic and non-asbestos organic (NAO). 1,2 Asbestos has been used for a long time in brake linings, but strictly prohibited due to its carcinogenicity in recent years. 3 Semi-metallic friction composites, as the most common brake lining materials, usually consist of a high amount of metallic components (typically >50%), covering iron powders, copper fibers, brass chips, molybdenite, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al [40] evaluated the flax fibers, basalt fibers and the friction surfaces in SEM images of brake pads reinforced with flax fibers. Moreover, Fan et al [41] found that the most abrasion was observed in the SEM images of the sample with the highest Al2O3 content. According to the SEM images, with the increase in temperature, the stibnite patch population on the friction surface increased and individual steel fibers were deformed and spread.…”
Section: Sem (Scabnning Electron Microscopy) Analysismentioning
confidence: 98%
“…On the other hand, the addition of Al2O3 in the friction material causes the sample to be less sensitive to temperature increases during sliding. Thus, it resulted in a stable friction coefficient [33]. Singh et al [34] reported that the presence of 5 wt.% Al2O3 in non-asbestos brake composite resulted in the highest friction stability (0.87) and friction variability (0.48).…”
Section: The S/n Ratio and Anova For Cof Stabilitymentioning
confidence: 99%
“…In previous studies, materials such as ZrSiO4 [13], Al2O3 [14][15][16], SiO2 [17], SiC [13], h-BN [18,19], Sb2S3 [20], MoS2 [21], and graphite [22] have been studied. These studies only focused on understanding the individual effects of abrasives and solid lubricants on the brake friction performances experimentally.…”
Section: Introductionmentioning
confidence: 99%